A SYSTEMATIC REVIEW OF FIVE HERBAL INGREDIENTS FOR THE MANAGEMENT OF DIABETES MELLITUS - RAHUL, GOPALAKRISHNAN; NANDHAKUMAR, ELUMALAI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Diabetes mellitus (DM) is becoming a common metabolic disorder which has serious threatening to public health that leads to huge economic loss in the developing countries. There are some antidiabetic drugs available that helps in controlling diabetes but there is no permanent remedy which reliefs to get completely cure from this disorder. By conducting huge number of research study, numerous herbal medicines have been found for diabetes. Extracts isolated from different natural resources especially plants have always been a rich arsenal for controlling and treating diabetes and its complication. Herbs used in the preparation of the polyherbal formulation were Cassia auriculata, Gymnema sylvestre, Syzygium cumini, Trigonella foenum-graecum, and Cinnamomum zeylanicum. Phytochemical qualitative analysis indicated the presence of flavonoids, alkaloids, terpenoids, tannins, steroids, carbohydrates and glycosides. So this review helps to understand the importance of five herbal ingredients present traditionally which can be used to treat DM.